Did you try squaring both sides? Why not square again?I need help with few sums !
if a+1/a= √ 2
then a^4+1/a^4 = ?
please do reply !
and if x^2+1/x^2=83
then x-1/x= ?![]()
It's just a normal IF and THEN problemTo start, those are not "sums".
In the 1st one (left side), I think you meant (a+1) / a;
if you don't understand what I'm saying,
then you need classroom help.
It's just a normal IF and THEN problem
the problem is actually :
\(\displaystyle \mbox{If }\, a\, +\, \dfrac{1}{a}\, =\, \sqrt{2\,}\, \mbox{ then find the value of }\, a^4\, +\, \dfrac{1}{a^4}\)
For the first problem, multiple through by a to get a quadratic equation in a, solve for a and do the a4. Or, you could just square a+1/a, rearrange and square again.I need help with few sums !
if a+1/a= √ 2
then a^4+1/a^4 = ?
please do reply !
and if x^2+1/x^2=83
then x-1/x= ?![]()
I do not get why you refuse to follow instructions and square both sides but rather place more posts. I am upset with this post and will just solve the problem. I hope that nobody minds my doing so.I need help with few sums !
if a+1/a= √ 2
then a^4+1/a^4 = ?
please do reply !
and if x^2+1/x^2=83
then x-1/x= ?![]()
Well, if that's the case, then no real solutions.
Dennis, in the end you might be right but look at how nice it worked out for me using a + 1/a =sqrt(2)Well, if that's the case, then no real solutions.
Rearrange as a quadratic:
a^2 - SQRT(2)a + 1 = 0
solve to get:
a = [SQRT(2) +- SQRT(-2)] / 2
That's a real mess!
I still think the problem is (a+1) / a = SQRT(2)
Then:
a + 1 = aSQRT(2)
aSQRT(2) - a = 1
a = 1 / [SQRT(2) - 1]
Incorrect. The solution is an Integer.
Ain't going to happen, tonight's beer and Star Gate night....Quit drinking :twisted:
Denis is correct in that there are no real solutions for a.
I'm evidently missing something...what zit thou meanest, Mark?
Maybe it was not a big deal but you did answer the wrong question.OK OK...I was only looking at solving a + 1/a = SQRT(2);
disregarded the remaining part...my fault...
multiply by a:
a^2 + 1 = aSQRT(2)
square both sides:
a^4 + 2a^2 + 1 = 2a^2
so:
a^4 = -1
a^4 + 1/a^4 = -1 + 1/(-1) = -2
Soooo....what was the big deal![]()